Histological evaluation of tissue reaction and new bone formation of different calcium silicate-based cements in rats - Bilge, K.; Atas, O.; Yildiz, S.; Calik, I; Dundar, S.; Atas, A. Gezer (Wiley, 2024)
Background: The purpose of this study was to evaluate the local reactions and new bone formation of rat subcutaneous and bone tissue to different calcium silicate cements. Methods: In this study, 80 rats were divided into five groups as control, BIOfactor MTA (BIO), NeoMTA Plus (NEO), MTA Repair Hp (REP), Biodentine (DENT) and then into two subgroups according to sacrification times (7, 30 days; n = 8). Polyethylene tubes filled with appropriate materials (test groups); empty tubes (control group) were implanted into the dorsum of each rat subcutaneously. For intraosseous implantation, materials were placed in the cavities created in tibia of rats. Subcutaneous tissue and tibia samples were stained with haematoxylin-eosin and subjected to histopathological analysis. A score (0-3) was used to grade inflammatory reaction and new bone formation. Data were analysed by Kruskal-Wallis and Mann-Whitney U tests (P < 0.05). Results: Inflammatory reaction observed in subcutaneous and intraosseous tissues for 7 days decreased significantly in all groups over time (P < 0.05). It was determined that there was significant increase in new bone formation in REP, BIO, DENT groups over time (P < 0.05). Conclusion: Four contemporary bioceramic materials induced local inflammation and tissues changes shortly after subcutaneous implantation, which were reduced over time. In intraosseous implantation, all materials induced new bone formation over time. (c) 2023 Australian Dental Association.
Keywords: Rat model; biocompatibility; calcium silicate cements; inflammation; new bone formation